LARANGAN PERKAWINAN SESAMA MARGA PARNA DALAM HUKUM ADAT BATAK TOBA (Studi Kasus di Kecamatan Alam Barajo Kota Jambi) - Ika Pramita Rusadi Dawolo; I Made Yudana; I Putu Windu Mertha Sujana (Program Studi PPKn Jurusan Hukum dan Kewarganegaraan Undiksha Singaraja, 2023)
This thesis is entitled Prohibition of Same-Marga Parna Marriage in Toba Batak Customary Law (Case Study in Alam Barajo District, Jambi City). This goal is motivated by differences in perspective between Batak customary law and national marriage law related to the rules of the marriage system, the prohibition on same-marga parna marriage which has become a tradition that continues to be preserved by the Batak indigenous people of Jambi City until now it is a phenomenon worthy of research. The purposes of this study (1) To find out and understand the implementation of the prohibition on same-marga parna marriages in Batak Toba customary law in Alam Barajo District, Jambi City (2) To know and understand the sanctions given to indigenous peoples who violate the prohibition on same-marga parna marriages in Alam Barajo District, Jambi City (3) To find out whether the marriage system according to Toba Batak customary law in Alam Barajo District, Jambi City is in accordance with the marriage system according to national law. This research is a descriptive qualitative research with data collection methods in the form of interviews, observation, and documentation studies. The location of this research was conducted in Alam Barajo District, Jambi City. Based on this research, the researchers found that there was a significant difference in perspective between the national marriage law (Law no. 1 of 1974) and Batak customary law. However, it was also found that there was compatibility between the national marriage law and Batak customary law regarding marriage rules.